Case Report: Analysis of colposcopic image features in a case of early-stage small cell neuroendocrine carcinoma of the cervix - Yuan, Leilei; Liu, Kejie (Frontiers in Oncology, 2026)
This study analyzes the colposcopy findings of an early-stage cervical small cell neuroendocrine carcinoma with ectopic kidney in a patient treated at Fuyang Peoples Hospital in October 2023. The colposcopic findings primarily included a well-defined, dense, thickened cervix with atypical and fragile blood vessels, along with irregular stromal infiltration. Pathological examination confirmed cervical small cell neuroendocrine carcinoma. The patient underwent a transabdominal radical hysterectomy with bilateral salpingectomy, pelvic lymph node dissection, and bilateral ovarian repositioning on October 5, 2023. No adjuvant therapy was administered postoperatively, and follow-up over 15 months showed no evidence of disease recurrence or metastasis. The study highlights the critical role of colposcopy in early detection of cervical small cell neuroendocrine carcinoma and its significant impact on improving patient outcomes.